Sarcopenia prevalence between obese and morbid obese patients in an obesity center: Prevalence of sarcopenia in obese middle-aged women - Tuna, Mujgan; Işık , Arzu Cennet; Hürmeydan , Ozlem (Journal of Surgery and Medicine, 2024)
Background/Aim: Sarcopenia and obesity are independent diseases that result in decreased muscle strength and function. Few studies have been conducted on the association of sarcopenia and obesity, especially in women. This study aims to measure the possibility of sarcopenic obesity in women with obesity. Methods: Our study was organized using a prospective cross-sectional study in Turkey. A total of 135 volunteer were included in the study. Inclusion criteria required the patients to have a BMI >35 kg/m2 or BMI >40 kg/m2 and no current comorbid disease. The exclusion criteria included: age (<18 and >70 years were excluded), history of muscle disease, malignancy, psychiatric disorders such as bipolar disease and psychosis, malnutrition, and recent corticosteroid (CS) use (within the last three months). Probable sarcopenia is determined by low skeletal muscle strength, and confirmed sarcopenia is defined if there is both low skeletal muscle mass and low skeletal muscle quality. Muscle strength was measured with isometric dynamometry using the handgrip method. A six-minute walk test (6MWT), in which we measured walking speed, was performed to determine the physical performance of the patients. We adjusted appendicular skeletal muscle (ASM) using height squared (ASM/height2) bioelectrical impedance analysis (BIA) to measure the muscle mass. Results: Patients’ mean age was 43 (11.4) (20-69) years. Of the total participants, 64.6% were in the age range of 40-59; 19.2% of patients were defined as possible sarcopenia; and 2.2% had confirmed sarcopenia. A total of 78.5% of patients did not meet any of the sarcopenia criteria. We determined that there was no difference in anthropometric measurements between sarcopenic and non-sarcopenic patients (P>0.05), except for waist and hip circumferences. However, we did observe a noteworthy distinction in waist and hip circumference measurements between the two groups, with sarcopenic patients exhibiting larger circumferences (P=0.05 and P=0.032, respectively). Our study revealed a significant disparity in the results of the six-minute walk test and handgrip strength values between sarcopenic and non-sarcopenic patients (P<0.001). Specifically, non-sarcopenic patients demonstrated higher values in both tests.. Conclusion: Obesity and sarcopenic obesity will continue to be a public health problem in the future among middle-aged women. It should be considered that the prevalence of decreased muscle strength was high in our study group, and physical performance decreased due to muscle strength. We concluded that as success in the six-minute walk test and handgrip values increased, the diagnosis of sarcopenia decreased, and each increase in platelet count increased the risk of sarcopenia in obese female patients.